АДВОКАТУРА УКРАИНЫ В КОНТЕКСТЕ ЕВРОПЕЙСКОЙ ПРАВОВОЙ РЕФОРМЫ. ПРОБЛЕМНЫЕ ВОПРОСЫ, ПУТИ РАЗВИТИЯ И УСОВЕРШЕНСТВОВАНИЯ - Мелихова, Юлия Александровна (SUPREMANCE OF LAW, 2017)
The article deals with issues related to the reform of the current system of advocacy in Ukraine. The main principles and priorities of reforming the institution of the Bar are determined. The current Ukrainian and international legislative acts ratified by Ukraine are listed, which define the concept of «professional rights of lawyers» and ««guarantees of advocacy», as well as regulate their protection. The necessity of creating a viable and effective complex system of legal remedies for lawyers’ rights is grounded in this work. Such a system should, fi rstly, consider issues of violation of rights and guarantees of lawyers and punish responsible persons for committed offenses and, secondly, to discourage and demotivate the commission of potential offenses against lawyers in the future. It must also cover the whole country territorially and be accessible to every lawyer. The list of typical current violations of statutory guarantees for professional advocacy, as well as provisions of domestic and international legislation regulating the protection of lawyers’ rights in the process of providing them with legal assistance to their clients is analyzed. Also in this article the author gives reasons why the statement that every violation of professional rights and guarantees of a lawyer is at the same time a violation of the human rights of his client, — is true. Particular attention is paid to the importance and necessity of making specific changes to some existing laws of Ukraine regarding the preservation of the independence of the advocate’s profession, strict observance of the rights and guarantees of the lawyer, improving the quality and strengthening the professional standards of its work. The importance of developing the activities of the National Bar Association of Ukraine as an allUkrainian professional organization that unites all advocates with the aim of ensuring the implementation of the tasks of the advocacy self-government is stressed by author.